Development of unified mathematical model of programming modules obfuscation process based on graphic evaluation and review method - Semenov, Serhii; Davydov, Viacheslav; Lipchanska, Oksana; Lipchanskyi, Maksym (Eastern-European Journal of Enterprise Technologies, 2020)
A set of algorithms of programming modules obfuscation is synthesized, which differs from the known ones by taking into account the variability of data types. This made it possible to describe these processes at the upper strategic level of formalization. The possibilities of using GERT models to apply various options of the distribution laws and their parameters in the transition from state to state are investigated. A unified GERT model of the programming modules obfuscation process is developed. This model differs from the known ones by the paradigm of using the mathematical apparatus of gamma distribution as the key one at all stages of modeling the obfuscation process. This made it possible to achieve model unification in the conditions of GERT network modification. The expectation and variance of the runtime of a random value of the obfuscation and deobfuscation time of programming modules are calculated. The results of the study showed that for the developed mathematical model, the addition of another obfuscation process leads to an increase in the runtime variance by 12 %, and when removed from the system, it decreases by 13 %. The runtime expectation changes exponentially. So, when removing the node, the expectation decreases by 9 %, and when increasing by 1 node, the expectation increases by 26 %. This shows the insignificance of changes in the studied characteristics under the conditions of model modification and confirms the hypothesis of model unification in conditions of using the mathematical apparatus of gamma distribution as the main one. These results allow the developer to predict the behavior of the programming modules protection system in terms of runtime. This allows reducing the time to decide on the feasibility of the obfuscation process